PREVALENCE OF ANTIMICROBIAL RESISTANCE AND VIRULENCE DETERMINANT OF SALMONELLAE ISOLATED FROM POTABLE WATER - MOHIT AGARWAL,; ANURAG JYOTI,; RAJESH SINGH TOMAR, (International Journal of Pharma and Bio Sciences, 2015)
The safety of drinking water in an urban city has been challenging since decades. Salmonellae are the enteric pathogens which survive even in treated drinking water. The pathogen harbors invA signature gene responsible for the virulence. Upon infection with Salmonellae, frequent antimicrobial therapy has lead the emergence of drug-resistant strains. The present paper aims to isolate and characterize drug resistant virulent isolates of Salmonellae from drinking water. We have collected drinking water from Gwalior, an important city of Northern India. Out of the five sites, three sites were contaminated with Salmonellae harboring invA gene. All the isolates from sites were resistant against at least 2 antimicrobials. Isolates from site 1, site 2 and site 5 were intermediates (reduced susceptibility) to different antimicrobials. These indicate possibilities of emergence of resistant strains in future. Our observation indicates the presence of drug-resistant isolates in drinking water of Gwalior. This has immense importance for microbial risk assessment.